STATE REGULATION OF REGIONS IN UZBEKISTAN AND ABROAD (ResearchJet Journal of Analysis and Inventions, 2021)
This article describes the requirements for state regulation of the economy, the need for it, the role of the state in economic development. As a developing country, Uzbekistan's economy is entering a market economy, and the role of the state is high. In particular, in the development of tourism, the main task of the state is to preserve the historical monuments of Uzbekistan, their modernization and attraction of tourists, and the work to be done in this direction.